Single-port surgery (SPS) strategy for small bowel obstruction (SBO) caused by postoperative internal hernia: A series case report. Issue 13 (March 2018) - Taniguchi, Kohei; Iida, Ryo; Ota, Koshi; Asakuma, Mitsuhiro; Uchiyama, Kazuhisa; Takasu, Akira
Abstract: Rationale: Internal hernia due to postoperative adhesions sometimes causes small bowel obstruction (SBO) and requires emergency surgery. The difficulties in the management of SBO with internal hernia include accurate diagnosis and estimation of its ischemic degree and of the risk of SBO recurrences following the surgical procedure. Laparoscopic surgery is a noninvasive to reduce postoperative adhesions and therefore has been widely used recently. However, surgeons often tend to hesitate in applying laparoscopic surgery for SBO because of some situational disadvantages such as poor operating space or iatrogenic bowel injury. Hence, laparoscopic surgery is still not yet the standard procedure for SBO caused by internal hernia. Thus, the establishment of an appropriate procedure for SBO due to internal hernia is required. Patient concerns: We experienced 3 SBO cases caused by postoperative internal hernia. The first patient was a 59-year-old man who had temporary loop-ileostomy for a perforated sigmoid colon due to diverticulitis. Severe hypogastralgia and vomiting occurred suddenly on the 33rd postoperative day. The second patient was an 81-year-old man who had been hospitalized due to epigastralgia of unknown origin. He had a surgical history of omentum patching for a perforated duodenum 20 years ago. The third patient was a 72-year-old female who presented at our hospital after sudden and severe hypogastralgia. She had a surgical history of sigmoidectomy for her sigmoid colon cancer 22 years ago. Diagnosis: A contrast computed tomography (CT) revealed a suspected closed loop obstruction of their bowels and immediate surgical treatments were required. Intervention: We tried SPS using the surgical glove method as an initial approach for their SBO caused by postoperative internal hernia. Outcomes: Two of these 3 cases completely underwent SPS treatment, which afforded accurate diagnosis of SBO. Laparotomy following SPS, which allowed accurate diagnosis, was judged to be appropriate and was performed in the third case. All the patients were discharged without any complications and SBO have not recurred after their discharge. Finally, we established a new strategy using SPS for SBO with internal hernia. Lessons: Our experience suggests that SPS is a promising strategy as an initial surgical approach for SBO with internal hernia.